(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aimed to present the functional and oncologic results of robotic assisted partial nephrectomy (RAPN) in clinical stage T1 tumors.Material and Methods: Fifteen patients who had undergone RAPN for T1a-b kidney tumor between July 2017 and January 2019 were included in the study. The demographic data, mean operation time, estimated blood loss, duration of warm ischemia, length of hospital stay and oncologic results were evaluated retrospectively.Results: Ten male and five female patients with a mean age of 55.4±7.6 (48-71) years were included in the study. A 4-port trans peritoneal approach was applied to all the patients. Nine right and six left renal masses with a mean tm diameter of 2.8±0.4 (2.4-3.6) cm were operated. The mean operation time was 217 (185-250) minutes, the mean blood loss was 225.6 (180-265) cc. Bleeding requiring transfusion was seen in one patient and a spontaneously resolved ileus was seen in another patient. Urethral stents were placed into two patients because the collector system was opened. 8 (53%) of renal masses were reported as renal cell carcinoma. Surgical margin positivity was identified in 2 (13%) of the patients. No local recurrence or distant metastasis was observed in any of the patients. None of the patients experienced incisional hernia and late complications. Conclusion: Robot-assisted partial nephrectomy is presently the gold standard treatment for patients with clinical stage T1 renal tumor. RAPN is an effective, safe and minimally invasive treatment modality in patients eligible for partial nephrectomy.